Team‐level identification predicts perceived and actual team performance: Longitudinal multilevel analyses with sports teams. (21st September 2018) - Thomas, William E.; Brown, Rupert; Easterbrook, Matthew J.; Vignoles, Vivian L.; Manzi, Claudia; D'Angelo, Chiara; Holt, Jeremy J.
Abstract : Social identification and team performance literatures typically focus on the relationship between individual differences in identification and individual‐level performance. By using a longitudinal multilevel approach, involving 369 members of 45 sports teams across England and Italy, we compared how team‐level and individual‐level variance in social identification together predicted team and individual performance outcomes. As hypothesized, team‐level variance in identification significantly predicted subsequent levels of both perceived and actual team performance in cross‐lagged analyses. Conversely, individual‐level variance in identification did not significantly predict subsequent levels of perceived individual performance. These findings support recent calls for social identity to be considered a multilevel construct and highlight the influence of group‐level social identification on group‐level processes and outcomes, over and above its individual‐level effects.